Disability and haptic mobile media. (October 2017) - Goggin, Gerard
This article examines haptic media from the standpoint of disability media studies. Its central case study is the smartphone moment, in which mobile communication emerges as a mass haptic media form. The smartphone as a form of haptic media engages dynamics of disability, including touch, vibration and proprioception. In particular, vibration is an important contribution of the smartphone to haptic media. Overall, the article argues that we need to understand the socio-technical dynamics of disability, and its complex relationships with senses and technology, in order to understand the histories that constitute current media – as well as to imagine future haptic mobile media.